2013
DOI: 10.1124/dmd.113.052126
|View full text |Cite
|
Sign up to set email alerts
|

Expression Variability of Absorption, Distribution, Metabolism, Excretion–Related MicroRNAs in Human Liver: Influence of Nongenetic Factors and Association with Gene Expression

Abstract: Genes that are important for the detoxification of drugs and other xenobiotics show a high degree of interindividual variation attributable to regulation by diverse genetic, nongenetic, and epigenetic mechanisms including microRNAs (miRNAs). We selected a set of 56 miRNAs predicted to target the 39-untranslated region of absorption, distribution, metabolism, excretion (ADME) genes to assess their hepatic expression levels and interindividual variability in a well-documented human liver tissue cohort (n = 92), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 61 publications
9
93
2
Order By: Relevance
“…In subjects with the C allele, AGT expression is decreased, which may eventually result in lower AGT levels. Similarly to AGT, miR-31 was shown to be expressed both in adipose tissue (Tang et al 2009) and in the liver, where the expression of miR-31 is higher in men than in women (Rieger et al 2013). The ''physical contact'' between miR-31 and angiotensinogen may thus occur both …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subjects with the C allele, AGT expression is decreased, which may eventually result in lower AGT levels. Similarly to AGT, miR-31 was shown to be expressed both in adipose tissue (Tang et al 2009) and in the liver, where the expression of miR-31 is higher in men than in women (Rieger et al 2013). The ''physical contact'' between miR-31 and angiotensinogen may thus occur both …”
Section: Discussionmentioning
confidence: 99%
“…The sex differences were also replicated in human fatty tissue (Park et al 2013) and may be linked to sex hormone regulation of AGT expression, which has been confirmed in laboratory rodents (Stavréus-Evers et al 2001;Ding et al 2001). The results of our study suggest that similar effects can be present in humans in the case of the ?11525 C/A (rs7079) polymorphism in miR-31 and miR-584 binding site of the angiotensinogen gene; sex-related differences in miRNA expression observed in the case of miR-31 (Rieger et al 2013) can be a contributing factor. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence documented that miRNAs play an important role in the modulation of the production of drug metabolizing enzymes and transporters through multi-directional interactions among environmental stimuli, the expression of miRNA molecules and genetic polymorphisms [26][27][28][29][30][31][32][33]. As miRNA expression has been reported to be affected by drugs and since miRNAs themselves may affect drug metabolism and toxicity, miRNA expression possesses a significant potential for affecting drug efficacy and drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs are associated with glucose metabolism, including miR122, miR34a, miR103/107, let-7 and miR143 (38). It has also been reported that miR122 and miR27b are associated with lipid metabolism, miR122, miR485-3p and let-7 are involved in iron metabolism, while miR132/142-3p/21, miR142-3p/21 and miR130b/185/34a are involved in the metabolism of drugs and xenobiotic substances (39). In conclusion, miRNAs play pivotal roles in regulating multiple aspects of liver physiology.…”
Section: Mirnas In Liver Development and Homeostasismentioning
confidence: 99%